Indonesian interference in students’ writing - Maya Irmalia (English Education Journal, 2016)
This research deals with Indonesian grammatical interference in students’ English writing. This research was designed to investigate: (1) the most common Indonesian grammatical interference found in English writing tasks done by students from 3 senior high schools in Sigli; and (2) the factors that caused these senior high school students in Sigli to have Indonesian grammatical interference. The subjects of this research were 86 first graders and three English teachers from three senior high schools; 29 students from SMAN Unggul Sigli, 27 students from SMAN 1 Sigli, and 30 students from MAN 1 Sigli plus 1 English teacher from each school. The data for this research was collected by using document analysis, a questionnaire, and interviews. The document analysis was in the form of students’ English writing papers about the description of their friends related to their appearance and/or their personality. The results from the document analysis showed that incorrect verb tenses, including subject-verb agreements were the most common Indonesian grammatical interference mistakes made by the students in their English writings – they were around 54% of all the interference mistakes found. Based on the results from the questionnaire and the interviews, it was found that most of the interference errors made by the students were caused by the students having too little practice to improve their English. Besides, the teachers did not provide the students with a good English environment which could help make them more familiar with English.